Continuing Education On Qualitative Risk Assessment: Improving The Understanding Of Risk - Ribeiro, Marcela G.; Bussacos, Marco A.; Filho, Walter dos R. Pedreira (European Scientific Journal, ESJ, 2016)
Despite a common agreement that environmental and occupational health & safety professionals must learn about risk early in formal education, such matters still remain underrepresented in most education programs. This paper describes the development and use of an instructional material aimed at exploring and improving health & safety professionals’ understanding on what risk really means, and on what is needed to its technical assessment. After reading a text depicting the technical and contextual aspects of unintended technological accidents, participants were asked to rank such events regarding its risk. Next, they had to explain what criteria they adopted, and also to compare their results with reference values, discussing the differences. Participants’ statements were collected and compiled. The ensuing discussion involved the resignification of the ideas raised by them, introducing the scientific meaning into a technical context. The proposed practice presented consistent results becoming an alternative resource to teach risk in a way participants share opinions based on their previous knowledge and begin to deal with the idea of evaluating risks in a scientifically reasoned basis.